The Legal Framework for Seizing Tradable Shares and Bonds in the Stock Market: An Analytical Study under Jordanian Law - Al-Frehat, Qais Faisal Ahmad; Al-Kasasbeh, Anas Badi Mufleh (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This study highlights the legal framework governing the seizure of negotiable shares and bonds as a means to satisfy creditors’ claims from the debtor’s assets held by third parties. It emphasizes the importance of these financial instruments in supporting economic activities and providing guarantees for creditors, which necessitates precise legal regulation. The research presents the legal nature of these securities under Jordanian law, analyzes the legal provisions regulating their seizure, and evaluates their adequacy in balancing the rights of creditors and debtors. Methods: The study adopts a descriptive-analytical approach to examine Jordanian legislation related to the seizure of shares and bonds by analyzing the relevant legal texts and assessing their practical effectiveness. Findings: The study found that the legal rules governing the seizure of shares and bonds differ from those applied to other assets due to their negotiable nature. Consequently, their sale must be conducted through the Securities Commission and the Amman Stock Exchange, rather than through public auction by the Execution Department as is customary for other assets. Moreover, the current legal framework does not comprehensively address all practical and procedural aspects of seizing shares and bonds. Conclusion: The study recommends amending Jordanian legislation to establish a clear legal framework that reflects the nature of shares and bonds as negotiable financial assets. It also calls for revisions to the seizure provisions in the Execution Law to close existing gaps and ensure the protection of the rights of all parties involved.